Psychiatric morbidities among youth (11-24 years) and its association with drug abuse: A cross-sectional study from Jammu - Mir, Muzaffar Hussain; Langer, Bhavna; Gupta, Riya; Kapoor, Anuj; Gupta, Rajiv Kumar; Hameed, Burhan (Indian Journal of Community Health, 2025)
Background: Knowledge is still scarce about mental health and psychiatric morbidities among youth with Substance Use Disorders (SUDs). Epidemiological studies indicate an association between SUDs and psychiatric morbidity. Aims and Objectives: The present study aimed to assess burden of psychiatric morbidities among youth and to determine their association with drug use. Methodology: This cross-sectional study was conducted among youth (11-24 years) who were attending the OPD in a tertiary care teaching hospital as a patient or an accompanying attendant to the patient. Psychiatric morbidity was measured by means of Depression Anxiety Stress Scale (DASS-21). Results: The results revealed that 20% of the youth were drug users. Among drug users, depression, anxiety and stress were present in 18.51% in comparison to 3.24% among non-users. Age, gender, residence, literacy levels and monthly family income were significantly associated with drug abuse (p<0.05). The medical problems commonly reported by surveyed youth included poor eye sight (42.5%), frequent headaches and dental problems (38.29%) and problem in sleeping (27.65%). Conclusion: Results of this study have revealed significant association between psychiatric morbidities and substance use. Among the psychiatric morbidities, anxiety and stress were found to be the most common among drug users.